The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/mrm.29642
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of low‐cost ultra‐low‐field MRI by dual‐acquisition deep learning 3D superresolution

Abstract: Recent development of ultra-low-field (ULF) MRI presents opportunities for low-power, shielding-free, and portable clinical applications at a fraction of the cost. However, its performance remains limited by poor image quality. Here, a computational approach is formulated to advance ULF MR brain imaging through deep learning of large-scale publicly available 3T brain data. Methods: A dual-acquisition 3D superresolution model is developed for ULF brain MRI at 0.055 T. It consists of deep cross-scale feature ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…In this study, we have implemented and demonstrated such an image formation method, PF-SR (26), applied to brain, spine, liver, and knee imaging, illustrating the ability of such data-driven image formation in enhancing image resolution while suppressing noise and artifacts. Our previous studies (23,26) and the preliminary brain and spine tests using synthetic datasets in this study have also shown the potential of applying this approach to datasets that contain brain and spine lesions.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In this study, we have implemented and demonstrated such an image formation method, PF-SR (26), applied to brain, spine, liver, and knee imaging, illustrating the ability of such data-driven image formation in enhancing image resolution while suppressing noise and artifacts. Our previous studies (23,26) and the preliminary brain and spine tests using synthetic datasets in this study have also shown the potential of applying this approach to datasets that contain brain and spine lesions.…”
Section: Discussionmentioning
confidence: 74%
“…Utilizing deep learning for enhanced image formation at 0.05 Tesla MR signal at 0.05 T is several orders of magnitude weaker than at 3 T, the standard highfield strength, due to its proportionality to field strength squared (B 0 2 ) (32), causing high image noise and poor resolution in ULF MRI. To overcome this challenge, we turned to computing and devised deep learning-based reconstruction methods for ULF MRI image formation that are driven by the large-scale high-field MRI data (23,26). We designed a partial Fourier super-resolution (PF-SR) method that integrates image reconstruction and super-resolution (fig.…”
Section: Shielding-free 005 Tesla Whole-body Mri Scanner Designmentioning
confidence: 99%
See 3 more Smart Citations